Hepatitis C Virus Driven AXL Expression Suppresses the Hepatic Type I Interferon Response - Read, Scott A. (PLoS One, 2015)
Treatment of chronic hepatitis C virus (HCV) infection is evolving rapidly with the development of novel direct acting antivirals (DAAs), however viral clearance remains intimately linked to the hepatic innate immune system. Patients demonstrating a high baseline activation of interferon stimulated genes (ISGs), termed interferon refractoriness, are less likely to mount a strong antiviral response and achieve viral clearance when placed on treatment. As a result, suppressor of cytokine signalling (SOCS) 3 and other regulators of the IFN response have been identified as key candidates for the IFN refractory phenotype due to their regulatory role on the IFN response. AXL is a receptor tyrosine kinase that has been identified as a key regulator of interferon (IFN) signalling in myeloid cells of the immune system, but has not been examined in the context of chronic HCV infection. Here, we show that AXL is up-regulated following HCV infection, both in vitro and in vivo and is likely induced by type I/III IFNs and inflammatory signalling pathways. AXL inhibited type IFNα mediated ISG expression resulting in a decrease in its antiviral efficacy against HCV in vitro. Furthermore, patients possessing the favourable IFNL3 rs12979860 genotype associated with treatment response, showed lower AXL expression in the liver and a stronger induction of AXL in the blood, following their first dose of IFN. Together, these data suggest that elevated AXL expression in the liver may mediate an IFN-refractory phenotype characteristic of patients possessing the unfavourable rs12979860 genotype, which is associated with lower rates of viral clearance.